Chemical structure designing to enhance the yield stress of electrorheological fluids based on modified chitosan compounds - Ko, YG; Choi, US; Sung, BH (WILEY, 2004)
For studying the influences of alkyl chain length, end groups of the side chains, and mixture on enhancing the shear stress of electrorheological (ER) fluids, chitosan carboxylates were synthesized for ER particles and prepared ER fluids by dispersing the particles in silicone oil. After comparing the shear stress of all prepared ER fluids, the conclusion obtained was that ER particles having two functional groups showed higher shear stress than those having one functional group. However, after mixing two ER particles having one functional group respectively, the ER fluid having those particles showed a lower shear stress. (C) 2004 Wiley Periodicals, Inc.